Assessing the efficiency of time-lapse cameras in collecting data on various life-history traits of two sympatric-nesting pelican species - Alexandrou, Olga; Catsadorakis, Giorgos (Macedonian Journal of Ecology and Environment, 2024)
Time-lapse cameras have been widely used in wildlife research in recent years to assist in data collection. Seven time-lapse cameras were installed on four Dalmatian pelican Pelecanus crispus and Great white pelican P. onocrotalus nesting islets at the Lake Lesser Prespa colony, NW Greece, during the 2015-2016 breeding period. The objectives were to assess the efficiency of this method in collecting data related to breeding phenology and breeding success, the seasonal and daily variation in attendance of adults of both species during the breeding season, the use of the islets by other bird species and mammals, and to document predation instances. We used Bushnell motion-triggered cameras, activated 24 hours a day, which also operated as time-lapse cameras, taking photos every half an hour during the daytime. At the end of the period, about 13,000 photos per camera were retrieved. Phenology dates documented with this method confirmed or enhanced results obtained with other methods. The attempt to estimate breeding success was not accomplished, due to the crèching behaviour of pelican chicks, combined with the inability to fully cover the nesting islets. Attendance of adult Dalmatian pelicans peaked from early February to early April. Respectively, attendance of adult Great white pelicans peaked from early April to early June. No significant differences were observed between day and night in attendance of either species. The islets also serve as a haven for Greylag geese Anser anser, mainly during the night for roosting and before the arrival of pelicans. At least four predatory mammals use the pelican nesting islets, but only prior to pelican arrival. The method is laborious and has various limitations and, although it provided some satisfactory results to our research questions, the effort involved is deemed excessive compared to other methods used for the same objectives at the Lesser Prespa Lake pelican colony.